Cairo and the printing press as the modes in the dissemination of Muhammad ‘Abduh’s reformism to colonial Malaya - Zakariya, Hafiz (IACSIT Press, 2011)
The second half of the 19th to the early 20th century witnessed the emergence of Islamic reformism as exemplified by Muhammad ‘Abduh (d.1905) and Muhammad Rashid Rida (d. 1935). These reformists urged the umma to revitalize their conditions –eliminate intellectual stagnation; to reform their morality, social life, economy and politics; and to reinterpret relevant aspects of the Islamic tradition to make it compatible with modern living. It not only made its way to the Middle East, but it also reached Southeast Asia. Muhammad ‘Abduh’s reformist ideas were brought to Malaya primarily through reform-minded students/scholars who studied in the Middle East, and the circulation of reformist writings such as al-Manār that reached audiences in Malaya. This paper examines the roles of Cairo and the printing press in the diffusion of Muhammad ‘Abduh ideas to Malaya